Las pérdidas y los duelos en personas afectadas por el desplazamiento forzado (2015)
ABSTRACT: The meaning attributed to the experiences of multiple losses, and the handling of grief in displaced persons in Medellin (Colombia) were analyzed. Method. Using a phenomenological-hermeneutical approach, a descriptive, qualitative study was carried out. Eighteen displaced persons, who voluntarily participated, reconstructed their experiences in semi-structured interviews. Atlas Ti software was used for data analysis. Results. Forced displacement causes multiple loss, both physical and symbolic. Pain, uncertainty, distrust, fear, somatic manifestations and isolation behavior are common responses to this experience and form a framework of the meanings built around it. Grief follows a process of partial management, according to personal characteristics, social support and the symbolic and economic resources available at the place of resettlement. Conclusion. Strength of attachment to the countryside and to other people, personal characteristics, contextual aspects and the way in which the bond was torn allow the understanding of the possibilities and limits for life reconstruction. However, some losses remain as wounds impossible to heal, generally those associated with horror-related experiences.